Pengaruh Promosi Digital Instagram dan Pengalaman Pelanggan Terhadap Kepuasan Pelanggan Aplikasi Pegadaian Digital Service di Cabang Cicalengka - Alawiyah, Sovi; Rizka Aula Assaf (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The development of digital technology encourages companies to utilize social media for promotion while enhancing customer experience through digital services. PT Pegadaian (Persero) has adapted by introducing the Pegadaian Digital Service Application and conducting digital promotion through Instagram. This study aims to analyze the effect of Instagram digital promotion and customer experience on customer satisfaction with the Pegadaian Digital Service Application at the Cicalengka Branch. This research uses a quantitative descriptive and verificative approach with a sample of 97 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with SPSS. The results show that Instagram digital promotion and customer experience have a positive and significant effect on customer satisfaction, both partially and simultaneously, with a coefficient of determination of 82.3%, while the remaining variance is influenced by other factors outside the study.